Development of an eco-friendly deinking process for the production of bioethanol using diverse hazardous paper wastes. (February 2020) - Saini, Sonu; Chutani, Preeti; Kumar, Prabhat; Sharma, Krishna Kant
Abstract: Bioethanol production using paper wastes seems a promising approach towards sustainable energy, but mainly hindered by hazardous ink. Therefore, in our experimental plan various methods were applied for the deinking of waste newspapers, laser printed papers and examination papers. A newly designed paper pulper reduced the pulping time from 6 h to 2 h. Cellulase (15 FPU/g) from Aspergillus oryzae MDU-4 was found effective for the deinking of newspapers, whereas laccase isozymes (150 U/g) from Ganoderma lucidum MDU-7 along with 2 mM HOBt was preferred for the ink removal and degradation from the examination papers. Ozonation in the presence of Tween-80 was found to be efficient in the removal of toxic toners used in laser printing papers. The biologically and physically deinked papers, studied with the help of SEM, TEM, FTIR, and XRD analysis revealed significant changes in the chemical and surface structure. Moreover, the saccharification of deinked papers with the help of an enzymatic consortium of Trichoderma citrinoviride MDU-1 resulted in 305 mg/g, 377 mg/g, and 409 mg/g release of sugars from the newspaper, examination paper, and laser printed paper, respectively. Finally, the enzymatic hydrolysates fermented with Saccharomyces cerevisiae NCIM-3640 produced 3.35 g/L ethanol, with 40.85% ethanol yield. Graphical abstract: Image 1 Highlights: Pulping time was reduced from 6 h to 2 h by designing a new pulp maker. Cellulase and laccase were effective for the deinking of NP and EP, respectively. Ozonation was found appropriate for the removal of toners from PP. Optimized deinking methods were comparatively better than chemical process. Ink free paper hydrolysates resulted in 40.85% ethanol yield using S. cerevisiae.